2022
DOI: 10.3889/oamjms.2022.8328
|View full text |Cite
|
Sign up to set email alerts
|

Survival of COVID-19 Patients Who Received Antiviral and Antiviral Therapy Combined with Anti-inflammation Therapy in a National Referral Hospital, Indonesia

Abstract: Background: COVID-19 has infected and spread over the whole earth. For the time being, there is no cure for COVID 19. Although several medications have the potential to be utilized at various stages of the disease, no therapy has yet been demonstrated to be completely successful. Aim: This study aims to determine survival of COVID-19 patients who received antiviral and antiviral therapy combined with anti-inflammation therapy in a national referral hospital Indonesia. Methods: COVID-19 patients tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Patients with a history of respiratory disease, such as COPD, have lower viral resistance and are more likely to develop acute respiratory distress syndrome (ARDS) (Saguil et al, 2020). Diabetes, hypertension, cardiovascular disease, and respiratory disease are all risk factors for disease development (Zheng et al, 2020;Afriani et al, 2022). This study's main strength was being the first study to the role of age and comorbidities on the outcome of confirmed clinically critical COVID-19 patients treated with remdesivir at one of Indonesia's national referral hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a history of respiratory disease, such as COPD, have lower viral resistance and are more likely to develop acute respiratory distress syndrome (ARDS) (Saguil et al, 2020). Diabetes, hypertension, cardiovascular disease, and respiratory disease are all risk factors for disease development (Zheng et al, 2020;Afriani et al, 2022). This study's main strength was being the first study to the role of age and comorbidities on the outcome of confirmed clinically critical COVID-19 patients treated with remdesivir at one of Indonesia's national referral hospitals.…”
Section: Discussionmentioning
confidence: 99%